Exploring Boron Difluoride Complexes of 2-Ketopyrroles - Pangiarella, Joel Ethan (Curtin University, 2025)
Boron difluoride complexes of 2-ketopyrroles have yet to gain popularity in literature and their analogues remain relatively few, with only nine boron difluoride complexes of 2-ketopyrroles reported. Moreover, an application for this class of compound has yet to be established. This work reports the synthesis and subsequent investigation of 10 boron difluoride complexes of 2-ketopyrroles.